The Effect of ROA and Composition of the Board of Commissioners on Earnings Quality with Earnings Management and Institutional Ownership as Intervening Variables - Badriyatul Hidayah; Subowo Subowo (Monex: Journal of Accounting Research, 2019)
The purpose of this study was to determine the relationship between ROA and the composition of the board of commissioners on earnings quality by mediating earnings management and institutional ownership. The research population is a company engaged in real estate and property listed on the Indonesia Stock Exchange in 2013 - 2015 as many as 48 companies. The determination of the research sample was based on purposive sampling and obtained as many as 38 samples. The data analysis method used is path analysis. The results show that ROA has a significant positive effect on earnings management; the composition of the board of directors has a significant negative effect on institutional ownership; earnings management has a significant negative effect on earnings quality. The results of the small test show that ROA has a significant negative effect on earnings quality through earnings management. Based on these conclusions, the advice that can be given is: management implements a corporate governance system in accordance with applicable regulations, treating institutional ownership variables as moderating variables.